Infection control and practice of standard precautions among hospital staff nurses in Indonesia - Meriem Meisyaroh Syamson; Murtini Murtini; Asnuddin Asnuddin; Yurniati Yurniati (Malahayati International Journal of Nursing and Health Science, 2021)
Background: Universal precaution as a strategy recommended by the Centers for Disease Control and Prevention in efforts to prevent infection and disease transmission among health workers, through the hospital Infection prevention and control (IPC) committee seeks to protect health workers and patients of the risk of transmitting the infection.Purpose: To determine the factors associated with the application of universal precautions in the prevention of infectious disease transmission in nurses at Lamaddukelleng Hospital, Wajo district.Method: A descriptive quantitative using cross-sectional design. The population is nurses at Lamaddukelleng Hospital, especially nurses in the emergency ward, with a total sampling of 28 respondents.Results: The Chi-Square test finding factor of nurses had a trained with p-value = 0.001 which shows that the nurses had a trained has a significant relationship to the application of universal precautions by nurses, while the availability of Infection prevention and control equipment facilities is p-value = 0.557 and the monitoring factor is p-value = 0.274, showing no relationship to the application of universal precautions by nurses.Conclusion: Shows that 75% of respondents have applied universal precautions. Suggestions to hospital management to be paying attention to provide Infection prevention and control equipment facilities and provide regular training, especially related to Infection Prevention and Control.